Планування часу виконання робіт у гібридних проєктах - Тригуба, Анатолій Миколайович; Кондисюк, Ігор Васильович; Коваль, Назар Ярославович; Тригуба, Інна Леонтіївна; Боярчук, Оксана; Боярчук, Олег Віталійович (Національний технічний університет "Харківський політехнічний інститут", 2022)
Обґрунтована структура нейронної мережі для планування природно-дозволеного фонду часу на виконання робіт впродовж життєвого циклу гібридних проєктів. Вона передбачає 5 входів, які відображають значення тривалості природно-дозволеного часу на виконання робіт у 5 попередніх добах, та 2 прихованих шари, що мають по 5 нейронів. Архітектура нейронної мережі передбачає використання багатошарово персептрона, виконання навчання із учителем та методу зворотного поширення похибки. Він базується на алгоритмі, який забезпечує мінімізацію помилки прогнозу завдяки поширенню сигналів помилки від виходів мережі (прогнозної тривалості фонду часу на виконання робіт) до її входів (значень тривалості фонду часу на виконання робіт у попередніх добах), в напрямку, який є зворотним до прямого поширення сигналів. Проведені дослідження на основі навчання нейронної мережі показують, що за кількості епох навчання понад 25000, похибка прогнозу не перевищує 4,8 %. Для навчання нейронної мережі використано статистичні дані літніх місяців 2020 року, які характерні для умов Володимир-Волинського району Волинської області.

The aim of the work is to substantiate the approach to forecasting the time fund for work in hybrid projects, taking into account the changing nature and climatic components of the design environment based on the use of neural networks. The neural network architecture involves the use of a multilayer perceptron, teacher training, and the method of backpropagation. It is based on an algorithm that minimizes the prediction error by propagating error signals from the network outputs (predicted duration of naturally allowed forecasting the working time fund) to its inputs (values of the duration of naturally allowed forecasting the working time fund in previous days), in the direction opposite to the direct propagation of signals. Based on the prepared initial data, the training of an artificial neural network was performed, which ensured the creation of an artificial neural network that is able to predict the duration of naturally allowed time to perform work in a software environment written in Python. Studies based on neural network training show that when the number of epochs increases to more than 25,000, the error does not exceed 4.8%. To study the neural network, we used the statistical data of the summer months of 2020 on the naturally allowed forecasting the working time fund during certain days, which are typical for the conditions of the Volodymyr-Volynskyi district of the Volyn region. The obtained results indicate that the use of the proposed architecture of the artificial neural network gives a fairly accurate forecast and this is the basis for making quality management decisions on planning the content and timing of work in hybrid projects.
Planning the time of performance of works in hybrid projects
Keywords: прогнозування; гібридні проєкти; штучні нейронні мережі; фонд часу; hybrid projects; time fund; forecasting; artificial neural networks